Listening to the accents of male native English speakers: ESL learners’ perceptions - Pilus, Zahariah; Zakaria, Nur Shahida; Zakaria, Muhamad Khairul (2015)
This paper investigates ESL learners’ perceptions and awareness of four different native English accents through an accent perception and survey task conducted on 66 Malaysian students who were enrolled in an English programme at a university in Trengganu. The participants responded to a questionnaire that was designed to examine their perceptions of British, American, Australian and New Zealand English accents and their abilities to identify them while or after listening to a recorded passage read by four male speakers, each speaking in one of the four accents. The participants were also asked to rate the speakers in terms of being an ideal English language teacher. In general, it was found that the participants rated the speakers whose accents were perceived to be more familiar more favourably than those whose accents were perceived to be less familiar to them. Compared to the rest of the speakers, the British English speaker was rated significantly higher as an ideal English language teacher. The participants also often misidentified the accents of the speakers and this finding supports that of previous studies (Scales, Wennerstorm, Richard & Wu, 2006; McGee, 2009) that accent identification is a complex task involving many factors such as past experiences.